2014
DOI: 10.1016/j.devcel.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Eya1 Interacts with Six2 and Myc to Regulate Expansion of the Nephron Progenitor Pool during Nephrogenesis

Abstract: SUMMARY Self-renewal and proliferation of nephron progenitor cells and the decision to initiate nephrogenesis are crucial events directing kidney development. Despite recent advancements in defining lineage and regulators for the progenitors, fundamental questions about mechanisms driving expansion of the progenitors remain unanswered. Here we show that Eya1 interacts with Six2 and Myc to control self-renewing cell activity. Cell fate tracing reveals a developmental restriction of the Eya1+ population within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
122
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 49 publications
10
122
0
Order By: Relevance
“…However, a Pax2 + Wt1 + MM still arises from the caudal trunk independently of this blockage. Lineage studies based on T and Eya1 (Taguchi et al, 2014;Xu et al, 2014) are consistent with the idea that the UB is derived from the rostral IM. However, their conclusions regarding the origin of the MM differ.…”
Section: The Regulation Of Mesoderm Patterning Along the Mediolateralsupporting
confidence: 63%
See 1 more Smart Citation
“…However, a Pax2 + Wt1 + MM still arises from the caudal trunk independently of this blockage. Lineage studies based on T and Eya1 (Taguchi et al, 2014;Xu et al, 2014) are consistent with the idea that the UB is derived from the rostral IM. However, their conclusions regarding the origin of the MM differ.…”
Section: The Regulation Of Mesoderm Patterning Along the Mediolateralsupporting
confidence: 63%
“…6). Lineage tracing of Eya1 + cells (Eya1-CreER×R26R-LacZ mice) showed that whereas E8.5-8.75 tamoxifen injection marked Eya1 + caudal IM, those cells did not give rise to ND, collecting ducts, rostral mesonephric tubules or kidney stroma cells (Xu et al, 2014). These cells did, however, give rise to caudal mesonephric tubules, to MM and to MM derivatives in the metanephros (Xu et al, 2014) (Fig.…”
Section: The Regulation Of Mesoderm Patterning Along the Mediolateralmentioning
confidence: 99%
“…Although Eya's tyrosine phosphatase is not required for normal development in Drosophila (Jin et al 2013), in mammals it dephosphorylates H2AX to promote repair and survival in response to DNA damage (Cook et al 2009;Krishnan et al 2009) and aPKCz to direct lung epithelial polarity and morphogenesis (El-Hashash et al 2012). Eya's threonine phosphatase is less well characterized, but appears to act both cytoplasmically to regulate innate immunity and nuclearly to provide transactivation and regulate the activity of other transcription factors (Okabe et al 2009;Liu et al 2012;Xu et al 2014;Jin and Mardon 2016).…”
mentioning
confidence: 99%
“…While shRNAmediated reduction of c-Myc expression to about 40% of the control level leads to a 2-fold decrease in the clonogenicity of PLZF-RARA-immortalized HSPCs (20), conditional ablation of c-Myc in BM cells leads to severe cytopenia and accumulation of HSCs (50), which suggests that expression levels of c-Myc are not simply correlated to self-renewal capacity. Previous study (29) suggests that c-Myc is one of the target genes of Eya, despite there being no direct evidence of transcriptional regulation, and a recent study (36) showed stabilization of Myc via dephosphorylation by the threonine phosphatase activity of Eya1. However, in PLZF-RARA-immortalized cells, neither the expression level of c-Myc transcripts nor that of c-Myc protein was affected by Eya2 depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the threonine phosphatase activity of Eya2, a recent study (36) showed that Eya1, which is homologous to Eya2, can stabilize c-Myc through dephosphorylation of phosphothreonine 58 (pT58) during (Fig. 12).…”
mentioning
confidence: 99%